Viver "à margem": as representações do (não) morar nas crônicas-reportagem de Eliane Brum - Andrade, Debora Gisele Gulak de (2020)
The main objective of this work is to analyze representations related to the theme of housing in chronicles-reporting by the author Eliane Brum. For this purpose, in order to establish comparisons, the observation of the theme in fictional texts by other authors is sought, starting from the context of the late 19th and early 20th centuries, when the expansion of cities requires changes related to the infrastructure of urban and local centers highlighting social inequalities. In the chronicles of Eliane Brum, published at the end of the 20th century and the beginning of the 21st, the writing procedures adopted by the author are verified in order to attract the reader to perceive the helplessness of those who live in precarious housing conditions or are homeless. As theoretical support, concepts related to nineteenth-century modernity and about “liquid” modernity were used. In this regard, the following authors were consulted: Zygmunt Bauman, Marshall Berman and Renato Ortiz. The beginning of the Republic in Brazil is contextualized, through the studies of Nicolau Sevcenko, Lilia Moritz Schwarcz, Flora Süssekind, Beatriz Resende and Cristiane Costa. The compositional aspects related to chronicle-reporting and the approximations between literature and journalism are developed through research by Rildo Cosson, Antonio Candido, José Marques de Melo, Marcelo Coelho and Luiz Carlos Simon. Regarding the implantation of the Belo Monte hydroelectric plant, wich led to the expulsion of riverside dwellers from Vale do Xingu, the study by Maíra Borges Fainguelernt supported the work. In the chronicles of Eliane Brum analyzed, there is a criticism about the violence with which the actions to implement the plant were carried out. The author routinely uses resources common to literature – poetic images, metaphors, intertextuality – as well as narrative procedures that highlight the individual and his story, such as descriptions related to his environment. Thus, writing has the function of maintaining the memory of what it was like to live in the Xingu and denounces the destruction that has occurred, seeking to raise awareness of the facts in the aesthetic valuation.